2022
DOI: 10.3390/molecules27072053
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils Derived from Cistus Species Activate Mitochondria by Inducing SIRT1 Expression in Human Keratinocytes, Leading to Senescence Inhibition

Abstract: Cistus L. is a genus of dicotyledonous perennial herbaceous plants. Cistus species have been commonly used in folk medicine in the Mediterranean region. In the present study, the biological activities of essential oils derived from Cistus species (Cistus laurifolius, C. monspeliensis, C. creticus, and C. salviifolius) were evaluated. Essential oils derived from C. laurifolius and C. monspeliensis were found to augment the expression of SIRT1, an anti-aging gene, in the normal culture of HaCaT cells. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Due to its large use in Mediterranean traditional medicines [6], the Cistus genus has been widely studied, revealing the presence of specialized metabolites endowed with antioxidant, antimicrobial, anti-inflammatory, and neuroprotective properties [3][4][5][6]10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its large use in Mediterranean traditional medicines [6], the Cistus genus has been widely studied, revealing the presence of specialized metabolites endowed with antioxidant, antimicrobial, anti-inflammatory, and neuroprotective properties [3][4][5][6]10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The glandular trichomes present on the leaves of these plants produce a characteristic resin named ladano, which is responsible for the aromatic scent and contains compounds of pharmacological interest [1,3,7]. Although each species has a distinct phytochemical profile, terpenoids (sesquiterpenes, diterpenes, monoterpenes), polyphenols (flavonoids, tannins, and phenolic acids), coumarins, and alkaloids are commonly found in the aerial parts of Cistus species [8][9][10][11]. Moreover, their essential oils contain mainly monoterpenes, sesquiterpenes, and diterpenes [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, several Cistus spp. oils significantly attenuated UVB-induced cellular senescence in a keratinocyte cell line (HaCaT) [87], while Cymbopogon nardus and Cymbopogon citratus oils showed cytoprotective properties on doxorubicin-induced senescence in the fibroblast-like kidney cell line (Vero) and fibroblasts (NIH/3T3) [88].…”
Section: Cellular Senescencementioning
confidence: 99%
“…de Carvalho et al [127] found that the essential oil of Eugenia uniflora promoted mitochondrial membrane dysfunction in Drosophila melanogaster by inhibiting oxidative phosphorylation. Similarly, essential oils isolated from several species of Cistus are reported to ameliorate ultraviolet-B-induced mitochondrial damage and cellular senescence in human keratinocytes [128]. Essential oils containing β-caryophyllene as a major constituent in plant species, such as Pterodon emarginatus, Aloysia citrodora, Syzygium aromaticum, Eplingiella fruticosa, Ocimum basilicum, and Salvia rosmarinus, have the potential to counter oxidative stress and mitochondrial dysfunction and have possible links to neuroprotection [129].…”
Section: Msleo Prevents Mitochondrial Membrane Potential (∆ψM) From L...mentioning
confidence: 99%